2018
DOI: 10.1021/acsenergylett.8b00687
|View full text |Cite
|
Sign up to set email alerts
|

Diammonium Cations in the FASnI3 Perovskite Structure Lead to Lower Dark Currents and More Efficient Solar Cells

Abstract: Hybrid halide perovskite solar cells with mixed cations demonstrate superior optical and electrical properties, especially for lead-based perovskite devices. Here, we report leadfree tin-based perovskite solar cells with diammonium cations, which can significantly improve the device performance. Formamidinium tin iodide (FASnI 3 ) perovskite can incorporate propylenediammonium (PN) and trimethylenediammonium (TN) and retain its three-dimensional structure while at the same time providing better film morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(151 citation statements)
references
References 55 publications
9
142
0
Order By: Relevance
“…The dark I–V curves of the solar cells without and with Sn 4+ reduction have also been measured, as shown in Figure S8, Supporting Information. The device with Sn 4+ reduction shows lower dark current at negative and positive bias voltages compared with the device without Sn 4+ reduction, suggesting improved charge transport and decreased recombination loss in the device, which is also in line with the reduced nonradiative recombination rate γ . The results of simulations by the modified detailed balance model and dark I – V characteristics have further confirmed that the reduction of Sn 4+ by Sn powder has substantially reduced the trap density of the mixed Pb–Sn perovskite films and finally led to the outstanding device performance of low‐bandgap mixed Pb–Sn PSCs.…”
supporting
confidence: 61%
“…The dark I–V curves of the solar cells without and with Sn 4+ reduction have also been measured, as shown in Figure S8, Supporting Information. The device with Sn 4+ reduction shows lower dark current at negative and positive bias voltages compared with the device without Sn 4+ reduction, suggesting improved charge transport and decreased recombination loss in the device, which is also in line with the reduced nonradiative recombination rate γ . The results of simulations by the modified detailed balance model and dark I – V characteristics have further confirmed that the reduction of Sn 4+ by Sn powder has substantially reduced the trap density of the mixed Pb–Sn perovskite films and finally led to the outstanding device performance of low‐bandgap mixed Pb–Sn PSCs.…”
supporting
confidence: 61%
“…Copyright 2018, Royal Society of Chemistry. k) Device structure, l) J – V curves, m) EQE curves, and n) PCE statistics of the FASnI 3 solar cells with and without 10% PN and 10% TN; Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…The FASnI 3 perovskite light absorbers incorporated with a diammonium cation such as propylenediammonium (PW) and trimethylenediammonium (TN) display better efficiency than the pristine FASnI 3 solar cell. The FASnI 3 light absorbers mixed with 10% TN and 10% PN displayed a SPCE of 5.53 and 5.58% with a better film morphology along with retaining their 3D perovskite structure . Figure shows the (k) device structure, (l) J –V curves, (m) EQE curves, and (n) PCE statistics of the FASnI 3 solar cells with and without 10% PN and 10% TN .…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…The increase in the V oc can be attributed to the reduction in Sn 4+ concentration which would result in a decrease in the carrier concentration and consequently reduced recombination and increased V oc . The space charge limited current (SCLC) method is used to evaluate the trap‐state density ( n t ) in the control and optimal perovskite films (see Supporting Information for details) . As shown in Figure S6, Supporting Information, the V TFL values of the devices without and with 5.0% TFEACl are around 0.22 and 0.14 V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Common approach is to use different additives to suppress the formation of Sn 4+ and thus reduce the hole density in the films, as well as improve the film uniformity and coverage. A variety of different additives have been reported to date, including various organic ammonium iodides, SnF 2 , and various reducing agents . The addition of SnF 2 , alone or combined with other additives, is a common approach to inhibit the formation of Sn 4+ and improve the film morphology.…”
Section: Introductionmentioning
confidence: 99%